A pilot study to evaluate the role of circulation CD4+ CCR6+ CRTh2+ cell in predicting risk of asthma in wheezing children - Jingyang Li; Jinhong Wu; Haipei Liu; Li Hua; Quanhua Liu; Dingzhu Fang; Yi Chen; Ruoxu Ji; Jianhua Zhang; Wenwei Zhong (BMC, 2021)
Abstract Background Wheezing is common in younger children and often related to viral infection. It is lack of reliable indicators for asthma prediction. Objective To evaluate the relationship between circulation CD4+CCR6+CRTh2+ memory Th2 cells and asthma diagnosis in wheezing children. Methods A prospective study was performed in children under 5 years old presented with wheezing or at last one episode of documented wheezing history. After inclusion, the level of serum allergen-specific serum IgE (sIgE) and circulating CD4+CCR6+CRTh2+cells were detected. The patients' personal and family histories of allergic disease were acquired by questionnaire. The children were followed up over 2 years. Diagnosis of asthma was assessed at the end follow-up. The risk factors in predicting asthma diagnosis were evaluated. Results A total of 43 children completed follow-up. Higher wheezing frequency were found in children with asthma diagnosis. The mean of circulating CD4+CCR6+CRTh2+cells in children diagnosed with or without asthma was 1.6 %±0.8 and 0.8 %±0.6 %, respectively, and was significantly higher in children diagnosed with asthma (p < 0.01). There was no significant difference between children with and without allergic diseases history or family allergic diseases in level of circulating CD4+CCR6+CRTh2+ cells. Logistic regression analysis indicated that circulating CD4+CCR6+CRTh2+ cells (EXP, 8.986; 95 % CI,1.886-42.816) and wheezing frequency(EXP, 0.127; 95 % CI, 0.023-0.703)were high risk factors for asthma. Conclusions Our exploratory study shown that circulating CD4+CCR6+CRTh2+ memory Th2 cells increased in asthma diagnosed children and it was a high-risk factor for asthma. Detection of this type of cells could be helpful in predicting the risk of asthma in wheezing children.